Implementing e-GP in Bangladesh: a perspective of works procurement in LGED - Sarker, Tarun Kumar (BRAC University, 2018)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2018.